2009
DOI: 10.1176/jnp.2009.21.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of the Rivermead Post-Concussion Symptoms Questionnaire in Mild-to-Moderate Traumatic Brain Injury Patients

Abstract: Posttraumatic brain injury patients with depressive symptoms were compared with nondepressed mild and moderate traumatic brain injury (TBI) patients based on their scores on the Rivermead Post-Concussion Symptoms Questionnaire (RPCSQ). A factor analysis demonstrated that the items of the RPCSQ loaded into three factors: mood and cognition, general somatic, and visual somatic symptom groups. Factor scores based on this model were calculated for each group and it was found that depressed subjects reported a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 37 publications
0
42
0
1
Order By: Relevance
“…Factor analyses have elicited a three-factor solution comprising cognitive, somatic, and emotional problems, 39 although variations have been reported. 40 The participants were asked to rate the severity of each symptom (currently compared with pre-injury levels) from 0 -''not experienced at all'' to 4 -''severe problem.'' The total score was used as the primary variable in this study.…”
Section: Emotional and Post-concussion Measuresmentioning
confidence: 99%
“…Factor analyses have elicited a three-factor solution comprising cognitive, somatic, and emotional problems, 39 although variations have been reported. 40 The participants were asked to rate the severity of each symptom (currently compared with pre-injury levels) from 0 -''not experienced at all'' to 4 -''severe problem.'' The total score was used as the primary variable in this study.…”
Section: Emotional and Post-concussion Measuresmentioning
confidence: 99%
“…We also hypothesised that patients with low social support and those engaged in litigation would be at greater risk of PCS. While the WHO cautions against the use of PCS, it remains accepted in both International Classification of Disease, 10th revision (ICD-10) and Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV),18 and it is commonly used in clinical practice. Therefore, we have continued to use it in this study.…”
Section: Introductionmentioning
confidence: 99%
“…11 Principal component analysis of the 22-item PCSS in a sample of 327 concussed athletes aged 12 to 25 years within the first week of recovery revealed a 4-factor solution that included a 7-item cognitive, 3-item sleep problem (ie, more or less sleep), 4-item emotionality, and 8-item somatic factor. 17 These researchers concluded that the emergent 4 factors may reflect different subtypes of concussion.…”
mentioning
confidence: 97%
“…Factor analytic statistical methods have been used by researchers to aggregate concussion symptoms into factors to better inform the clinical assessment and management of sportrelated concussions. 11,18,19 The use of concussion symptom factors, which comprise similar individual symptoms, is intuitive to clinicians and patients and may better inform and provide a more targeted approach to the assessment, management, and treatment of concussions, particularly for concussion symptoms that linger beyond 21 days. For example, a concussed athlete presenting predominately with cognitive symptoms (eg, difficulty concentrating, memory problems) may benefit from different management and treatment programs relative to a patient with a postinjury migraine presentation or affective presentation.…”
mentioning
confidence: 99%